The (N)Ever-Changing World: Stability and Change in Organizational Routines - Pentland, Brian T.; Hærem, Thorvald; Hillison, Derek (Organization Science, 2011)
This paper uses data on invoice processing in four organizations to distinguish empirically between two competing theories of organizational routines. One theory predicts that routines should generate patterns of action that are few in number and stable over time, and that atypical patterns of action are driven primarily by exceptional inputs. The competing theory predicts the opposite. By modeling the routines as networks of action and using a first-order Markov model to test for stationarity, we find support for the competing theory. The routines generated hundreds of unique patterns that changed significantly during a five-month period without any apparent external intervention. Changes did not appear to reflect improved performance or learning. Furthermore, we found that exogenous factors (such as large invoices from unusual vendors) are not associated with atypical patterns of action, but endogenous factors (such as the experience of the participants) are. We also found that increased automation can increase variation under some circumstances. These findings offer empirical support for endogenous change in organizational routines and underscore the importance of the sociomaterial context in understanding stability and change.